Análise do poliformismo A(1188)C do gene da Il-12β em pacientes com hanseníase e em uma amostra de um grupo controle da população do estado do Pará - PEREIRA, Renato Malheiros (2022)
Leprosy is a chronic infectious disease caused by Mycobacterium leprae, an acid fast, rod-shaped bacillus. This bacterium infects, mainly, the interior of macrophages and Schwann cells. Leprosy is an endemic disease, observed specially in tropical countries and underdevelopment, where the poverty is configured as an important factor of risk. However it must be considered that only 10% of the infected people will develop the illness, which can be related to a possible susceptibility genetics still not clarified. In this work, was investigated the association of polymorphism A(1188)C in the IL-12 gene in different clinical forms, multibacillary (MB) and paucibacillary (PB), and in a control sample. The purpose was to verify if there were genetic differences statistically significant. It was included, in this work, 116 individuals with leprosy (96 with MB form and 20 with PB form) and 117 healthy individuals, these last were chosen in a randon way in the population of Belém – Pará and was considered as the control group. It was not found significant differences between the two forms of leprosy, MB and PB. However, when it was related the group of patients with the control group, it was demonstrated significant differences. According to logistic regression, it was found association between alelle 1188*C and leprosy susceptibility.